188k views
1 vote
If f(x) = 2x - 6 and g(x) = 3x+ 9, find (i - g)(x).

User VinyJones
by
5.1k points

2 Answers

5 votes

Answer:

5x+3

Step-by-step explanation:

(f+g)(x)=f(x)+g(x)=2x−6+(3x+9)=5x+3

So we just add the expressions.

please bran-list for my virtuous answer

User Osama Aftab
by
5.5k points
6 votes

Answer:

assuming your question is (f-g)(x), the answer will be as follows.

Since you are asked to find the difference between the two functions,

(f-g)(x)=(2x-6)-(3x+9)

=2x-6-3x-9

=-x-15, this is the answer

or simply

(f-g)(x)=-(x+15)

User TheWolfNL
by
5.1k points